Back Cover: A Porous Organic Polymer Nanotrap for Efficient Extraction of Palladium (Angew. Chem. Int. Ed. 44/2020). Issue 44 (31st August 2020) - Aguila, Briana; Sun, Qi; Cassady, Harper C.; Shan, Chuan; Liang, Zhiqiang; Al‐Enizic, Abdullah M.; Nafadyc, Ayman; Wright, Joshua T.; Meulenberg, Robert W.; Ma, Shengqian
Abstract : Through a systematic investigation of pyridine‐based porous organic polymers, structural modifications of the monomer unit were found to create a nanotrap selectively capturing palladium in solution, as reported by Q. Sun, S. Ma, and co‐workers in their Communication on page 19618 . By creating a stronger complex with palladium through intramolecular hydrogen bonding, this vital element could be extracted through recycling plants and waste streams.